The Immunomodulatory Metabolite Itaconate Regulates NLRP3 Inflammasome Activation and Type I Interferon Signalling - Hooftman, Alexander (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2021)
The NLRP3 inflammasome is a multi-protein complex which activates caspase-1 for the cleavage and release of mature IL-1β and IL-18. Caspase-1 also cleaves gasdermin D, driving a process called pyroptosis. Results from clinical trials have demonstrated the utility of anti-IL-1β therapy in reducing the incidence of cardiovascular events and lung cancer, and blocking IL-1β has shown clinical utility in the treatment of classically IL-1β-driven pathologies such as cryopyrinassociated periodic syndromes (CAPS). There is therefore a strong interest in targeting NLRP3 with small molecules, several of which are in development. Indeed, murine models have implicated the NLRP3 inflammasome in various autoinflammatory diseases, including Alzheimer’s disease, Parkinson’s disease and type I diabetes. Itaconate has emerged as a prominent metabolite in macrophages activated with the gram-negative bacterial product lipopolysaccharide (LPS). It has been shown to elicit immunomodulatory effects via modification of target cysteines and activation of the transcription factor NRF2. Here I have investigated the effect of itaconate on NLRP3 inflammasome activation. I have shown that itaconate is an endogenous inhibitor of NLRP3 inflammasome activation. The cell-permeable itaconate derivative 4-octyl itaconate (4-OI) blocked NLRP3 inflammasome-induced IL-1β release, pyroptosis and ASC oligomerisation in murine macrophages, but had little effect on AIM2 and NLRC4 inflammasome activation. Irg1-/- macrophages, which lack endogenous itaconate, exhibited heightened NLRP3 inflammasome activation. Conversely, Irg1 overexpression in an inflammasome reconstitution model reduced inflammasome activation. These data suggest that endogenous itaconate also inhibits inflammasome activation. These effects were not dependent on NRF2. 4-OI modified a specific cysteine (C548) on NLRP3 and inhibited the NLRP3-NEK7 interaction which is required for inflammasome activation to take place. 4-OI also blocked inflammasome activation in human PBMCs isolated from both healthy volunteers and CAPS patients, suggesting that itaconate may be harnessed therapeutically for the treatment of NLRP3-driven disorders. I also examined the non-canonical inflammasome, which activates caspase-11. Caspase-11 is induced by LPS via type I interferon signalling and directly senses intracellular LPS to promote pyroptosis. I have found that 4-OI, but not unmodified itaconate, inhibits type I interferon release, signalling and subsequent caspase-11 expression. 4-OI inhibited non-canonical inflammasome-induced pyroptosis by blocking the upregulation of caspase-11 in response to LPS. As caspase-11 is an interferon-stimulated gene (ISG), reduced caspase-11 expression with 4-OI was due to reduced type I interferon release in response to LPS. Interestingly, itaconic acid treatment actually boosted LPS-induced IFN-β production and Irg1-/- macrophages released less IFN-β upon LPS stimulation. These results reveal a clear difference between 4-OI and unmodified itaconate. 4-OI also blocked caspase-11 induction following IFN-β stimulation, which I found was due to reduced JAK/STAT signalling. ACE2, the host cell entry receptor for SARS-CoV- 2, is also an ISG and its upregulation in airway epithelial cells was similarly blocked by 4-OI. Taken together, these results provide further evidence of the immunoregulatory role of itaconate. I have found evidence of metabolic regulation of the NLRP3 inflammasome, and in 4-OI I have described a specific pharmacological inhibitor of NLRP3 activation. 4-OI also inhibits type I interferon release and signalling, a property not shared by unmodified itaconate. These results in particular highlight some of the current issues associated with the study of itaconate biology and further our knowledge of this important immunometabolite, derivatives of which might have potential in the treatment of autoinflammatory diseases.
APPROVED
Keywords: Immunometabolism; Inflammasome; Metabolite; Itaconate; Inflammation; Macrophage; IL-1β